Novel Predictors of Future Vascular Events in Post-stroke Patients—A Pilot Study - Schrick, Diana; Ezer, Erzsebet; Tokes-Fuzesi, Margit; Szapary, Laszlo; Molnar, Tihamer (Frontiers in Neurology, 2021)
Introduction: A modified platelet function test (mPFT) was recently found to be superior compared to impedance aggregometry for selection of post-stroke patients with high on-treatment platelet reactivity (HTPR). We aimed to explore some peripheral blood cell characteristics as predictors of recurrent ischemic episodes. The predictive value of mPFT was also assessed in a cohort followed up to 36 months regarding recurrent ischemic vascular events. Methods: As a novelty, not only whole blood (WB), but after 1-hour gravity sedimentation the separated upper (UB) and lower half blood (LB) samples were analyzed including neutrophil antisedimentation rate (NAR) in 52 post-stroke patients taking clopidogrel. Area under the curve (AUC, AUCupper and AUClower respectively) was separately measured by Multiplate in the WB, UB and LB samples to characterize ex vivo platelet aggregation in the presence of ADP. Next, the occurence of vascular events (stroke, acute coronary syndrome, ACS) were evaluated during 36-month follow-up. Results: A total of 11 vascular events (stroke n=5, ACS n=6) occurred during the follow-up period. The AUCupper was significantly higher in patients with recurrent stroke compared to those with uneventful follow-up (p=0.03). The AUCupper with a cut-off value ≥70 based on the mPFT, was able to predict all stroke events (p=0.01), while the total vascular events were independently predicted by NAR with a sensitivity of 82% and specificity of 88%. Conclusions: A combination of NAR reflecting the inflammatory state and AUCupper indicating HTPR may provide a better prediction of recurrent ischemic events suggesting a better selection of patients at risk, thus providing an individually tailored vascular therapy.